SYNTHESIS AND EVALUATION OF 7-(2-((SUBSTITUTED PHENYL) IMINO)-2-PHENYLETHOXY)-4-METHYL-2H-CHROMEN-2-ONES AS ANTIFUNGAL AGENTS (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
In the context of the dangerous phenomenon of antimicrobial resistance to the available drugs, we present here the synthesis and evaluation of 7-(2-((substituted phenyl) imino)-2-phenylethoxy)-4-methyl-2H-chromen-2-ones as antifungal agents. Among the compounds, SB-4 was found to be most potent against Candida albicans when compared with the reference drugs Clotrimazole and Terbinafine. The molecular properties of the newly target compounds were performed by online software, and results showed good drug-like properties. The results showed target compounds further optimized as lead compounds as anti-Candida potential.